(untitled) (World Bulletin of Public Health, 2022)
In the literature, members of the genus Cistanche salsa (Chenopodiaceae) of the Chistanche family, in particular, halloxylon, are parasitize on the roots of Circassian plants. There are 9 species of this genus in Uzbekistan and 4 species in Karakalpakstan, all of which are parasitic plants